Nightingale Point - Goldie, Luan (HQ an imprint of HarperCollins Publishers Ltd, 2019)
"On an ordinary Saturday morning in 1996, the residents of Nightingale Point wake up to their normal lives and worries. Mary has a secret life that no one knows about, not even Malachi and Tristan, the brothers she vowed to look after. Malachi had to grow up too quickly. Between looking after Tristan and nursing a broken heart, he feels older than his twenty-one years. Tristan wishes Malachi would stop pining for Pamela. No wonder he's falling in with the wrong crowd, without Malachi to keep him straight. Elvis is trying hard to remember to the instructions his care worker gave him, but sometimes he gets confused and forgets things. Pamela wants to run back to Malachi but her overprotective father has locked her in and there's no way out. It's a day like any other, until something extraordinary happens. When the sun sets, Nightingale Point is irrevocably changed and somehow, through the darkness, the residents must find a way back to lightness, and back to each other."--Publisher description.